Sosialisasi dan Pelatihan Pengisian Formulir Merek - Edy Purwanto; Mohammad Herli; Rizal Andi Sya’bana; M. Munir Syam AR (BERDAYA: Jurnal Pendidikan dan Pengabdian Kepada Masyarakat, 2022)
Pagerungan Besar is one of the villages in the Sapeken District with abundant potential so Pagerungan Besar is transformed into a village that gives birth to many great entrepreneurs. The business existence also has problems with the brand. Thus, this activity aims to provide understanding to business actors in Pagerungan Besar Village about the importance of marks and the process of filling out forms in trademark registration. Activities carried out are in the form of socialization and training in filling out brand forms. This method is considered appropriate to solve the problems experienced by business actors. The implementation of this activity goes through several stages, namely the preparation stage, the implementation stage, and the activity evaluation stage. From the results of the socialization and training carried out, information was obtained that increased participants' understanding of the material provided. Thus, it was concluded that the activities carried out at the Pagerungan Besar Village Hall regarding the socialization and training of filling the brand were declared successful. For further activities, it is necessary to provide assistance to business actors until the trademark registration is carried out until the certificate processing is completed.